2010
DOI: 10.1155/2011/749627
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract of Chinese Propolis Facilitates Functional Recovery of Locomotor Activity after Spinal Cord Injury

Abstract: An ethanol extract of Chinese propolis (EECP) was given intraperitoneally to rats suffering from hemitransection of half of their spinal cord (left side) at the level of the 10th thoracic vertebra to examine the effects of the EECP on the functional recovery of locomotor activity and expression of mRNAs of inducible nitric oxide (NO) synthase (iNOS) and neurotrophic factors in the injury site. Daily administration of EECP after the spinal cord injury ameliorated the locomotor function, which effect was accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…All RNA samples were treated with DNase I to remove contaminating genomic DNA. Semi-quantitative RT-PCR was performed as described previously (22) to assess mRNA levels of nerve growth factor (NGF), BDNF, and neurotrophin (NT)-3, with β-actin mRNA used as the internal control. The amplification was carried out with a thermal cycler at 94°C for 5 min, followed by 24-38 cycles consisting of 94°C for 30 s, 60-65°C for 1 min, and 72°C for 45 s. The sequences of primers, annealing temperatures, and size of PCR products were the following: β-actin, 5'-GTGGGCCGCTCTA GGCACCAA-3' (forward) and 5'-CTCTTTGATAT CACGCACGAT-3' (reverse), 63°C, 542 bp; NGF, 5'-GGCAAGTCAGCCTCTTGTAG-3' (forward) and 5'-GGCAAGTCAGCCTCTTCTTGTAGCCTT CC-3' (reverse), 60°C, 376 bp; BDNF, forward primer, 5'-CCCAGGGCAGGTTCGAGAGG-3' (forward) and 5'-CCGCCAGACATGTCCACTG-3' (reverse), 61°C, 350 bp; NT-3, 5'-TTACCAGAGCACCCTG CCCAAA-3' (forward) and 5'-ACCTGGTGTCCCC GAATGTCAA-3' (reverse), 61°C, 348 bp.…”
Section: Methodsmentioning
confidence: 99%
“…All RNA samples were treated with DNase I to remove contaminating genomic DNA. Semi-quantitative RT-PCR was performed as described previously (22) to assess mRNA levels of nerve growth factor (NGF), BDNF, and neurotrophin (NT)-3, with β-actin mRNA used as the internal control. The amplification was carried out with a thermal cycler at 94°C for 5 min, followed by 24-38 cycles consisting of 94°C for 30 s, 60-65°C for 1 min, and 72°C for 45 s. The sequences of primers, annealing temperatures, and size of PCR products were the following: β-actin, 5'-GTGGGCCGCTCTA GGCACCAA-3' (forward) and 5'-CTCTTTGATAT CACGCACGAT-3' (reverse), 63°C, 542 bp; NGF, 5'-GGCAAGTCAGCCTCTTGTAG-3' (forward) and 5'-GGCAAGTCAGCCTCTTCTTGTAGCCTT CC-3' (reverse), 60°C, 376 bp; BDNF, forward primer, 5'-CCCAGGGCAGGTTCGAGAGG-3' (forward) and 5'-CCGCCAGACATGTCCACTG-3' (reverse), 61°C, 350 bp; NT-3, 5'-TTACCAGAGCACCCTG CCCAAA-3' (forward) and 5'-ACCTGGTGTCCCC GAATGTCAA-3' (reverse), 61°C, 348 bp.…”
Section: Methodsmentioning
confidence: 99%
“…The neuroprotective effect of CAPE has been mainly attributed to its immunemodulatory, anti-inflammatory and antioxidant properties (Kasai et al, 2011;Araujo et al, 2012;Natarajan et al, 1996;Noelker et al, 2005). Additionally, it has been shown that artepillin C, a component of propolis, stimulates neurite outgrowth in PC-12m3, a mutant cell line irresponsive to NGF (Kasai et al, 2011;Kano et al, 2008). However, despite the neuroprotective potential of CAPE, its effect on neurite outgrowth has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Female Wistar rats (7 weeks of age, weighing 120-140 g; Japan SLC, Hamamatsu, Japan) were used in this study, and they were handled in accordance with the Guidelines of Experimental Animal Care issued by the Office of the Prime Minister of Japan. The surgery was performed according to the method reported previously (11,13,15). Briefly, the rats were anesthetized with sodium pentobarbital (40 mg/kg body weight), after which the spinal cord (left side) was hemi-transected or not (sham control) by use of microsurgical scissors after laminectomy at the level of the 10th thoracic vertebra.…”
Section: Methodsmentioning
confidence: 99%
“…Locomotor function of the left hindlimb was assessed by the Basso, Beattie, and Bresnahan (BBB) locomotor rating scale in open-field as described earlier (3). Evaluation was performed 1 day after injury and subse-assessment of bilaterally impaired hindlimb function following contusive SCI, but it has been also used for lateral hemi-transection SCI (11,13,15). Hemitransection of the spinal cord resulted in complete paralysis of the hindlimb ipsilateral to the transection side (left) for several days in all groups.…”
Section: Methodsmentioning
confidence: 99%